The benefits of one‐dimensional detectors for high‐pressure powder X‐ray diffraction. (3rd December 2015) - Fisch, Martin; Lanza, Arianna; Macchi, Piero; Casati, Nicola
Abstract : High‐pressure powder X‐ray diffraction is a fundamental technique for investigating structural responses to externally applied force. Synchrotron sources and two‐dimensional detectors are required. In contrast to this conventional setup, high‐resolution beamlines equipped with one‐dimensional detectors could offer much better resolved peaks but cannot deliver accurate structure factors because they only sample a small portion of the Debye rings, which are usually inhomogeneous and spotty because of the small amount of sample. In this study, a simple method to overcome this problem is presented and successfully applied to solving the structure of an L‐serine polymorph from powder data. A comparison of the obtained high‐resolution high‐pressure data with conventional data shows that this technique, providing up to ten times better angular resolution, can be of advantage for indexing, for lattice parameter refinement, and even for structure refinement and solution in special cases.